2022
DOI: 10.1002/dta.3239
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the stability of 17 psychoactive drugs in a “simulated postmortem blood” model

Abstract: In the postmortem environment, some drugs and metabolites may degrade due to microbial activity, even forming degradation products that are not produced in humans. Consequently, underestimation or overestimation of perimortem drug concentrations or even false negatives are possible when analyzing postmortem specimens. Therefore, understanding whether medications may be susceptible to microbial degradation is critical in order to ensure that reliable detection and quantitation of drugs and their degradation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(60 citation statements)
references
References 89 publications
(140 reference statements)
1
59
0
Order By: Relevance
“…Compared with the quantitative experiment, 27 degradation was similar after 5 days at 37°C in the qualitative experiment, that is, ZIPR degraded to below the LOD of the LC‐DAD method in all blood specimens.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Compared with the quantitative experiment, 27 degradation was similar after 5 days at 37°C in the qualitative experiment, that is, ZIPR degraded to below the LOD of the LC‐DAD method in all blood specimens.…”
Section: Resultsmentioning
confidence: 81%
“…The majority of chemicals and materials have been described previously 27 . Ammonia (analytical grade, 30%) and ethyl acetate (99%) were obtained from ChemSupply (Gillman, SA, Australia).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, in a study to investigate microbial degradation of lurasidone in postmortem blood, our research group found that LURA degraded in unpreserved ante-mortem whole blood inoculated with human feces when incubated at 37 C or stored at ambient temperature. 18 It was established that Clostridium perfringens and Bacteroides spp. dominated these specimens, with the former reported to dominate postmortem specimens 19,20 and the latter previously reported in postmortem blood.…”
mentioning
confidence: 99%